Peran Staf Administrasi dalam Penguatan Budaya Keselamatan Pasien Rumah Sakit - Didit Setiawan (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Patient safety is often viewed exclusively as the responsibility of clinical personnel. However, administrative errors occurring during the admission process and documentation stages constitute major contributors to medical risk. This study aims to explore the strategic role of administrative staff in strengthening patient safety culture and mitigating medical risks through effective communication coordination. A narrative literature review was conducted extensively using the Scopus, PubMed, and Web of Science databases, covering publications from 2014 to 2024. Data were analyzed using a thematic synthesis approach. The findings identify four main themes: administrative staff as information gatekeepers, the role of health information technologies (HIS/EMR) in bridging communication gaps, collaboration barriers arising from hierarchical structures, and the need for an Interprofessional Shared Governance framework. Administrative accuracy in the early phases of care is proven to be critical in preventing latent errors with potentially fatal consequences. Strengthening patient safety culture requires the integration of administrative staff through cross-departmental training, standardized communication protocols, and non-punitive incident reporting systems. Administrative staff are not merely bureaucratic support personnel but are key actors within the modern hospital patient safety ecosystem.